THE INFLUENCE OF ORGANIZATIONAL CULTURE AND LEADERSHIP ON EMPLOYEE PRODUCTIVITY IN FREIGHT FORWARDING COMPANIES JAKARTA - Nawiyah, Nawiyah; Endrawati, Titin (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to explore employee productivity. Good employee productivity is increasing over time. Employee productivity is influenced by many factors, including organizational culture and leadership. Organizational culture and leadership play an important role in an organization. Organizational culture provides guidelines for employees because it will help develop a sense of belonging for employees, can be used to develop personal relationships with the organization. Good leadership and proper organizational culture development, the organization will be able to avoid complex problems, namely the working relationship between leaders and subordinates, so that work productivity can be achieved. This study uses the method of validity test analysis, reliability test, multiple linear regression and hypothesis testing with t-test and F-test. The population in the study were employees where APP Polytechnic students did industrial work practices at freight forwarder companies with 60 respondents. The results of this study are that organizational culture variables have a positive and significant effect on employee productivity, leadership variables have a positive and significant effect on employee productivity. Together, organizational culture variables and leadership variables also have a positive and significant effect. Keywords: organizational culture, leadership, employee productivit